Effects of Hydrology on Fish Diversity and Assemblage Structure in a Texan Coastal Plains River. Issue 1 (26th November 2018) - Bower, Luke M.; Keppeler, Friedrich W.; Cunha, Eduardo R.; Quintana, Yasmin; Saenz, David E.; Lopez‐Delgado, Edwin O.; Bokhutlo, Thethela; Arantes, Caroline C.; Andrade, Marcelo C.; Robertson, Clinton R.; Mayes, Kevin B.; Winemiller, Kirk O.
Abstract: High‐flow pulses affect river ecosystem dynamics in many important ways including by forming connections between the channel and oxbow lakes. This study assessed the influence of discharge on fish assemblage structure and diversity in the channel and oxbows of the Guadalupe River, Texas. Local assemblages of two oxbows and two channel sites were surveyed using standardized methods to test four hypotheses: (1) assemblage structure in oxbow lakes differs from those in the river channel, (2) α diversity decreases during extended periods of low discharge, (3) β diversity decreases during high discharge and increases during extended periods of low discharge, and (4) species turnover and assemblage nestedness decline during periods of high discharge. We found evidence to support the first three hypotheses. Unsurprisingly, lotic‐adapted fishes were observed more frequently in the river channel, whereas lentic‐adapted species generally were more common in the oxbow lakes. Species richness declined during periods of low discharge possibly due to harsher environmental conditions or stronger species interactions (e.g., predation). Discharge was inversely associated with both β diversity and species turnover, suggesting a stronger mass effect during high‐flow pulses, and stronger species sorting during low‐flow conditions. Contrary to our fourth hypothesis, assemblage nestedness increased during periods of high discharge. Finally, we also found evidence to support the hypothesis that species turnover decreased as discharge declined. The results of this study demonstrate the importance of flow pulses for maintaining fish diversity and assemblage structure in floodplain river systems. With additional research involving more sites and longer time series, it should be feasible to define and identify thresholds for flow regime changes that alter assemblage structure and species diversity.